THE CHANGING OBJECTIVES OF ACCOUNTING. - Daines, H. C. (The Accounting Review, 1929)
Abstract The article focuses on the changing objectives of accounting. There has been considerable discussion among accountants concerning such questions as the proper basis or bases for valuing balance sheet items, what constitutes income, what are proper elements to be included in costs and the responsibility of the accountant for furnishing statistical information on internal operations. The author examines some of the objectives of accounting with a view to ascertain if such a consideration may shed additional light to these questions. According to the author, much of use controversy would disappear if it is recognized that there are widely different purposes and problems for which accounting information is necessary and that the particular information which is needed will vary from one problem to another. The most orthodox view with reference to general accounting is that accounting records should be kept so as to reflect that income which is legally available for dividends the view is particularly concerned with realized income. This generally supposed to mean recognized in the accounts only when a sale is complete.